Levantamento e análise crítica dos conflitos socioambientais na Mesorregião do Baixo Amazonas (2014-2019) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The objective of this study was to carry out a socioenvironmental conflicts survey in the Lower Amazon region. The research had an exploratory descriptive approach. The analysis was carried out in two online phases on the socio-environmental conflicts for the territorial regions caused by the implantation of enterprises, in the municipalities that are part of the Lower Amazonas Meso-region, occurring between 2014 and 2017 when the key words were linked to research theme. The second phase consisted of the analysis of documents of the Pastoral Commission of Youth (CPT). They were filtered as the information communicating the results of the study and data compilation and analysis. The results indicate that there is an exchange rate of the municipalities of Oriximiná and Almeirim, the municipalities of the Santarém and Prainha rivers, Óbidos and Monte Alegre, and with lower Juruti and Mojui scores of the fields. The stakeholders are involved in the conflicts, are family farmers, quilombolas, indigenous and riverside and agro-extractive settlements. The distinction between the types of entrepreneurship of Oriximiná continues to be highlighted in distinguishing the categories of distinct enterprises, are five different types of enterprises (Madeireira, Livestock, Construction of dam and mining) that affect three types of class (quilombolas, rural workers , indigenous quilombolas). When doing a survey, a mesoregion of the lower Amazon, a trail of activities in timber and mining activities, leaving no blank, works of art linked to the land and agricultural issue, involving a soybean and a firm land, as there is one hour, relentless pursuit of business in expanding its agribusiness.
Keywords: Conflitos; Socioambientais; Amazônia; CNPQ:: Ciências Biológicas; Conflitos Socioambientais